Correlation between semen quality and the seminal biochemical markers: alpha-glucosidase, fructose, and zinc in infertile men compared with a normal population of men - Rochdi, Chaymae; Nasr, Fahd A.; Elrherabi, Amal; Bellajdel, Ibtissam; Taheri, Hafsa; Bouhrim, Mohamed; Al-zharani, Mohammed; Qurtam, Ashraf Ahmed; Saadi, Hanane; Mimouni, Ahmed; Choukri, Mohammed (Frontiers in Endocrinology, 2025)
IntroductionThe male reproductive tract's accessory glands produce seminal biochemical markers that can help diagnose reproductive disorders and assess male fertility. This study evaluated the relationship between seminal biochemical components and sperm parameters in 150 men, including 20 normospermic individuals and 130 infertile patients classified into oligozoospermia, azoospermia, asthenozoospermia, teratozoospermia, and oligoasthenoteratozoospermia (OAT) groups. MethodsThe patients underwent semen analysis and measurements of fructose, neutral alpha-glucosidase (NAG) and zinc in seminal plasma. Results and discussionsThe level of fructose was significantly decreased in asthenozoospermic and increased in oligoasthenoteratozoospermic (OAT) men. It was significantly correlated with semen volume, sperm concentration, progressive motility and morphology. Seminal neutral -glucosidase and zinc levels were found significantly reduced in azoospermic and OAT patients. The seminal NAG levels were significantly correlated with semen volume and progressive motility. For zinc level, the concentration was significantly correlated with sperm concentration (r = 0.041, p < 0.001).